TOURIST POTENTIAL OF KASHKADARYA REGION - Togaymurodova Naila Bahrom qizi (Journal of new century innovations, 2023)
Abstract: In this article, we will discuss the tourist attractions that have formed in different regions of Kashkadarya region.